2017
DOI: 10.13189/ujer.2017.050904
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Investigation of the Curriculum Evaluation Theses Completed between the Years 2006-2015 in Turkey

Abstract: The aim of this research is to examine postgraduate theses on curriculum evaluation completed between the years 2006-2015 in Turkey in terms of various aspects such as university, year, curriculum which is evaluated, curriculum evaluation model, research method, design, sample type, data collection methods, data analysis technique. In order to determine the theses, a comprehensive review was made through the thesis database of Council of Higher Education (COHE). 306 postgraduate theses were used as data source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…It was determined that, after Educational Sciences, thesis for the evaluation of curricula were completed in the field of Basic Education. Aslan and Sağlam (2017) reached a similar result in their research for theses on curriculum evaluation. According to the study, while most of the theses based on curriculum evaluation were completed at educational sciences division, a significant number of them were realized at basic education division.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…It was determined that, after Educational Sciences, thesis for the evaluation of curricula were completed in the field of Basic Education. Aslan and Sağlam (2017) reached a similar result in their research for theses on curriculum evaluation. According to the study, while most of the theses based on curriculum evaluation were completed at educational sciences division, a significant number of them were realized at basic education division.…”
Section: Discussionmentioning
confidence: 52%
“…In parallel with this, the theses on curriculum evaluation, included in the research, were written in the institutes of educational sciences (n = 303) and social sciences (n = 242). Also, in the studies carried out for the postgraduate theses completed in Curriculum and Instruction (CI), it was found that the universities such as Abant İzzet Baysal, Anadolu, Ankara, Atatürk, Fırat, Gazi, Hacettepe, and METU produced more theses in that field in the last fifteen years (Aslan & Sağlam, 2017;Kozikoğlu & Senemoğlu, 2016;Özüdoğru, 2018;Yetkiner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…İncelenen çalışmalarda veri analizi tekniği olarak çoğunlukla betimsel istatistikler ve fark analizlerinin kullanıldığı, ileri istatistik yöntemlerinin kullanıldığı kestirimsel analizlerin çok az kullanıldığı belirlenmiştir. Bu sonuçlar eğitim araştırmalardaki eğilimlerin analiz edildiği çeşitli çalışmaların (Aslan & Sağlam, 2017;Gökmenoğlu, 2015;Kayan & Adıgüzel, 2017;Kurt & Erdoğan, 2015) sonuçlarıyla genel olarak tutarlık göstermektedir. Çalışmada ulaşılan bu sonuçların yanı sıra; değerlendirilen program olarak ya günümüz eğitim siteminde ortaokul düzeyine denk gelen sınıfların programlarının değerlendirildiği ya da ilköğretim programının genel olarak değerlendirildiği tespit edilmiştir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified